System-Theory-Based-Model-Building for a practice and theory of alpine skiing - Haag, H. (Science and Skiing IV, 2009)
INTRODUCTION: The purpose of this analysis is to explain "Alpine Skiing" with the help of system-theory-based considerations in their practical and theoretical dimensions, thus integrating theory and practice in regard to the sport "Alpine Skiing" (Haag, 1994; Haag, 2004).